The Osteoinductivity of Calcium Phosphate-Based Biomaterials: A Tight Interaction With Bone Healing - Zhang, Yuchen; Shu, Tianyu; Wang, Silin; Liu, Zhongbo; Cheng, Yilong; Li, Ang; Pei, Dandan (Frontiers in Bioengineering and Biotechnology, 2022)
Calcium phosphate (CaP)-based bioceramics are the most widely used synthetic biomaterials for reconstructing damaged bone. Accompanied by bone healing process, implanted materials are gradually degraded while bone ultimately returns to its original geometry and function. In this progress report, we reviewed the complex and tight relationship between the bone healing response and CaP-based biomaterials, with the emphasis on the in vivo degradation mechanisms of such material and their osteoinductive properties mediated by immune responses, osteoclastogenesis and osteoblasts. A deep understanding of the interaction between biological healing process and biomaterials will optimize the design of CaP-based biomaterials, and further translate into effective strategies for biomaterials customization.